Analysis of Th17 and Tc17 Frequencies and Antiviral Defenses in Gut-Associated Lymphoid Tissue of Chronic HIV-1 Positive Patients. (28th June 2015) - d'Ettorre, Gabriella; Ceccarelli, Giancarlo; Andreotti, Mauro; Selvaggi, Carla; Giustini, Noemi; Serafino, Sara; Schietroma, Ivan; Nunnari, Giuseppe; Antonelli, Guido; Vullo, Vincenzo; Scagnolari, Carolina
Abstract : The complex relationship between both the Th1/Th17 and Tc1/Tc17 axis and innate defences in the intestinal mucosa during HIV-1 infection has not been well characterized. This study examined the frequency, phenotype, and functional status of T cell populations in the gut-associated lymphoid tissue and peripheral blood of virologically suppressed HIV-1-infected patients on therapy, focusing on the Th1, Th17, Tc1, and Tc17 cell subsets. We found a persistent immune cell activation (CD38 and HLADR expression) into the GALT despite the higher levels of Th17 and Tc17 in respect to peripheral blood. An upregulation of type I IFN response in GALT compared to the peripheral blood compartment was also recorded. Furthermore, IFN- α / β levels were negatively related to the frequencies of Th1 naïve cells and Tc1 cell subsets (naïve, central memory, and effector memory) in the GALT. In contrast, no relationships between type I IFN response and Th1 or Tc1 cell subsets in peripheral blood compartment and between IFN- α / β and Th17/Tc17 in both GALT and peripheral blood district were recorded. These data indicate that prolonged antiretroviral treatment improves GALT immune function despite the persistence of immune activation and type I IFN response in chronic HIV-1 positive patients.